Covering Theorem for Alternating Groups - Sh. S. Al-Bundi (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2005)
For the alternating group An J. L. Brenner, through a series of papers showed that the class C of n- cycle or (n-1)- cycle, CCC covers A, for n = 4k - 1, 4k and 4k + 1, In this paper, the contumacy class of type (2)(n-2),n>6and n 1S even was studied. This class splits into two classes of A, c denoted by C and C, CCC= C’C’C was found.